2015
DOI: 10.15376/biores.11.1.54-70
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extractives on Digestibility of Cellulose in Corn Stover with Liquid Hot Water Pretreatment

Abstract: Many herbaceous lignocelluloses suitable for ethanol production have high extractives contents, such as some straws and corn stover. The high extractives content might affect pretreatment or enzymatic hydrolysis. In this study, extractives were removed from corn stover, and then extractives-free corn stover and ordinary corn stover were respectively pretreated using a liquid hot water (LHW) method and hydrolyzed to evaluate the effect of extractives on cellulose digestibility. Extractives-free corn stover pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Before the acid pretreatment, raw OTB was subjected to an aqueous extraction in order to remove soluble components like extractives, avoiding the formation of complex lignin-carbohydrates (Ballesteros et al 2011). Li et al (2016) also tested the effect of removing water extractives from corn stover, and determined a significant increase in the enzymatic digestibility after liquid hot water pretreatment.…”
Section: Feedstockmentioning
confidence: 99%
“…Before the acid pretreatment, raw OTB was subjected to an aqueous extraction in order to remove soluble components like extractives, avoiding the formation of complex lignin-carbohydrates (Ballesteros et al 2011). Li et al (2016) also tested the effect of removing water extractives from corn stover, and determined a significant increase in the enzymatic digestibility after liquid hot water pretreatment.…”
Section: Feedstockmentioning
confidence: 99%
“…In the first stage (≤100°C), free water and bound water in the sample begin to evaporate. In the second stage (160°C‐240°C), the extracts with low thermal stability begin to decompose, and the temperature rises further to the superposition region of cellulose and hemicellulose, resulting in severe weight loss . And this process is mainly endothermic .…”
Section: Resultsmentioning
confidence: 99%
“…In the third stage (≤290°C‐400°C), the residue began to carbonize, and the weight loss rate decreased compared with the previous stage . Moreover, the DTG curves showed that there was a platform at 240°C‐290°C for raw corn stover, which was caused by the separation of the DTG peaks of extractives, cellulose, and hemicellulose . On the other hand, as shown in the TGA curve of corn stover after alkali treatment, it can be seen that the pyrolysis temperature and weight loss rate of corn stover after alkali treatment increased significantly, and the corresponding absorption peak caused by extractives and hemicellulose almost disappeared in the DTG curve, while the corresponding absorption peaks of cellulose increased.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations